IMPROVING CONTEXTUALIZED PROBLEM-SOLVING SKILLS IN 8TH GRADE STUDENTS THROUGH "DIGESTIVE SYSTEM" PROBLEM-ORIENTED LEARNING - Alfanisa Dwi Pramudia Wardani; Wirawan Fadly; Martinez David (INSECTA: Integrative Science Education and Teaching Activity Journal, 2024)
Problem solving ability is one of the competencies that must be achieved by students to reach sustainable development goals (SDGs). There is a need for more appropriate learning methods and education policies in Indonesia to improve literacy and numeracy skills, including problem-solving competencies, which is fundamental in this era of Industrial Revolution 4.0. Science Education for Sustainable Development (SESD) focuses on developing learners' attitudes and competencies to alleviate life and find an innovation that is relevant to a problem. This study investigated whether Digestive System learning designed to be oriented towards contextual problems with SESD-based direct teaching promotes learners' ability to solve contextual problems better than conventional classroom learning. Data collection included assessment with tests on learners' problem-solving skills through quasi-experimental research using a pretest-posttest experimental control group design. The experimental group received learning about the digestive system with a problem-oriented learning model and the SESD approach. The research sample was the VIII grade students of SMPN 4 Ponorogo. The pre-test scores for the experimental and control groups were similar, at 66.4 and 67.0 respectively. However, the experimental group had a higher post-test score of 82.0, while the control group had an average score of 73.0. Supported by Cohen's d analysis of 0.60 shows that problem-based learning (PBL) with the SESD approach is more effective than conventional learning in improving students' problem-solving skills.